Anaesthetic Challenges in Cardiac Interventional Procedures - Thangavel, Periyasamy; Muthukumar, Siva; Karthekeyan, Baskar R.; Vakamudi, Mahesh; Nayagam, Hemananand (Scientific Research, 2014)
The increasing scope of interventions in the cardiac catheterization laboratory (CCL) and electrophysiological laboratory (EPL) has resulted in new challenges for the anaesthesia teams where they deal with different patient categories, complications and safety issues. Collaboration and planning between cardiologist and anaesthesiologist are required for both patient safety and procedural success. This review aims to discuss procedures performed in interventional cardiology and the importance of anaesthesiologists in managing such patients. Percutaneous interventions are being increasingly performed in adult as well as in pediatric patients. Procedures are usually done under mild to moderate sedation. General anaesthesia is required in certain conditions and also in pediatric patients. Knowledge of echocardiography, individual disease condition and fluoroscopy is important. Anaesthesiologists are assuming an increasingly important role in the multidisciplinary management of complex patients and interventions. A comprehensive understanding of procedures is essential to provide a high level of anaesthetic care and maintain patient safety
Keywords: Cardiac Catheterization; Electrophysiological Laboratory; Percutaneous Interventions; Offsite Anesthesia; Pediatric